Online Privacy And Government - Harry Henderson
Recent revelations of extensive government surveillance programs pit privacy concerns against the need to fight terrorism and crime. Using cases involving real people, this book explores how federal agencies, local law enforcement, and even schools are collecting, usingand perhaps abusingthe personal information they gather online. The book concludes with a discussion of proposed regulations and policies that could strike a better balance between privacy and security.